Aquaporin Expression in Colonic Mucosal Biopsies From Irritable Bowel Syndrome With Diarrhea - Camilleri, Michael (Clin Transl Gastroenterol, 2019)
Aquaporin (AQP) channels are involved in regulating fluid homeostasis in the colon. Several AQP channels were detected in human colon epithelial cells. In a previous study, rats fed 1% (wt/wt) sodium cholate had increased AQP3, 7, and 8 levels, suggesting AQP involvement in bile acid diarrhea (BAD). Our aim was to compare AQP expressions in rectosigmoid mucosal (RSM) biopsies from patients with irritable bowel syndrome–diarrhea (IBS-D) (divided into those with normal or high fecal BA excretion) and in patients with IBS-constipation (IBS-C) compared with healthy controls. METHODS: In RSM biopsies from 44 patients with IBS-D (with normal (<) or high (>2,337 μmol/48 hours (BAD)) fecal BA excretion), 10 patients with IBS-C, and 17 healthy controls, we measured expressions of AQP1, 3, 7, and 8, with RT-PCR (housekeeper gene GAPDH). We analyzed RNA for expression by RT(2)-PCR assays, with expression calculated using 2(−ΔΔCT)-based fold-change. Comparisons of IBS groups were corrected for false detection rate (Bonferroni correction for 12 comparisons; P < 0.0042). AQP protein measurements on biopsies from 3 healthy controls, 3 patients with IBS-D, and 3 patients with BAD were performed by western blots (GAPDH housekeeping protein). RESULTS: In RSM from patients with IBS-D (but not IBS-C), mRNA expression of AQP3 was decreased, and AQP7 and 8 were increased relative to controls. Fold differences were not different in IBS-D with or without BAD. Western blots confirmed increased expression of AQP7 and 8 and decreased AQP3 proteins in biopsies from patients with IBS-D compared with controls. CONCLUSIONS: Increased AQP7 and 8 and decreased AQP3 expressions in RSM suggest that further studies on AQPs' potential role in the pathophysiology of diarrhea in IBS-D are warranted.